Experimental Study on Microscale Simulation of Oil Accumulation in Sandstone Reservoir - Ren, Dazhong; Zhang, Hanpeng; Wang, Zhenze; Ge, Bingyu; Liu, Dengke; Zhang, Rongjun (Frontiers in Physics, 2022)
It is generally believed that conventional hydrocarbon accumulates in sandstone traps after migrating at a certain distance. Unconventional hydrocarbon only migrates at a short distance before accumulation or be imbibed in the tiny pores of shale and tight sandstone reservoir, and there is no obvious trap boundary. There are also different views on the time interval between hydrocarbon accumulation and migration. In this paper, microscale simulation experiments are used to study the process of oil accumulation during migration. In the single pore-throat model, oil can 100% saturate the pore in the process of migration with continuous oil supply. In the plane sandstone model, when oil migrates through the entire model, the oil-bearing area can reach more than 50% of the model area. In the sandstone reservoir model, when the front edge of oil migrates through the entire sandstone layer, the oil saturation near the injection point can reach more than 90%, while the oil saturation of the front part of the model is only about 50%. It shows that in sandstone reservoir, when there are sufficient oil source and continuous charging pressure, the oil saturation near the charging point continues to increase during oil migration, and the range of high oil-bearing area continues to expand. Therefore, there can be a certain number of hydrocarbon accumulations along the migration path in sandstone reservoir under sufficient oil supply and continuous charging pressure, rather than just in traps.